IT education: impact assessment of a multi-fold approach - Radaideh, Moh’d A.; Abu Al-Haija, Qasem (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study addresses the benefits and challenges of implementing a multi-faceted hybrid approach to delivering an introductory information technology (IT) course at Jordan University of Science and Technology, Jordan. We conducted a questionnaire survey with 251 participants, utilizing Google Forms for data collection and Microsoft Excel 2016 for coding. Data analysis was performed using SPSS statistics 17.0. Most participants were male students aged 21-23, pursuing bachelor’s degrees across various departments, with network engineering and security (NES) being the most represented. The survey items exhibited good internal consistency (Cronbach’s alpha=0.778), and significant associations were found among variables (p-value<0.05). Strengths of the hybrid approach include flexibility, instructor responsiveness, and engaging online resources. However, areas for improvement were identified in online discussion forums, such as technology tool usability, workload management, communication clarity, and assessment transparency. Despite challenges, the study underscores the successful implementation of the hybrid approach in IT course delivery, supported by positive student perceptions and recommendations for future adoption.